2008
DOI: 10.1177/1049732307312305
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Contraceptive Use and Pregnancy Prevention Among Women in the U.S. Navy

Abstract: In this article we present the results of a study to illuminate the explanatory factors related to unplanned pregnancies in the United States Navy, particularly with regard to female contraceptive training and practices, and occupational culture. The data set consists of 52 semistructured interviews with key informants, sailors, and enlisted personnel who were recruited via a quota sample stratified by gender, occupation, and location. The research team carried out semistructured interviews at seven different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Multivariate analyses for past year sexual behaviors also adjusted for binge drinking in the last year because this variable has also been associated with sexual behavior. 11,35 All analyses were weighted to account for the survey design, and statistical tests were at a twosided alpha level of 0.05. Analyses were completed using SAS software and STATA 12.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses for past year sexual behaviors also adjusted for binge drinking in the last year because this variable has also been associated with sexual behavior. 11,35 All analyses were weighted to account for the survey design, and statistical tests were at a twosided alpha level of 0.05. Analyses were completed using SAS software and STATA 12.…”
Section: Discussionmentioning
confidence: 99%
“…These women reported feeling stigmatized as promiscuous if they requested condoms and believed their male counterparts to be exempt from the same criticism. 24 They also reported not using condoms because if found this would be evidence of violation of the policy prohibiting sexual activity while deployed. 24 Multiple sexual partners.…”
Section: Introductionmentioning
confidence: 99%
“…24 They also reported not using condoms because if found this would be evidence of violation of the policy prohibiting sexual activity while deployed. 24 Multiple sexual partners. Although there are limited data on high-risk sexual practices among military women, some studies have reported a high prevalence of new or concurrent sexual partners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among deployed soldiers, sexual contact within the unit is strongly discouraged, if not prohibited (Brown, 2008;Duke & Ames, 2008). This prohibition of sexual activity while deployed may inadvertently discourage soldiers from using condoms, as they are not easily disposed of in an environment where used condoms or wrappers may become evidence (Duke & Ames, 2008). Gendered double standards also affect condom use; rnale contraceptive use may be seen as indicative of sexual prowess, whereas female use of protective measures may be seen as an indication of promiscuity (Duke & Ames, 2008).…”
Section: Military Culture and Sexualitymentioning
confidence: 99%